Comparative evaluation of desensitizing efficacy of dentifrice containing 5% fluoro calcium phosphosilicate versus 5% calcium sodium phosphosilicate: A randomized controlled clinical trial - S Ashwini; K Swatika; D N Kamala (Wolters Kluwer Medknow Publications, 2018)
Background: A considerable number of agents are effective in the treatment of dentin hypersensitivity (DH). The present 2 months' randomized clinical trial compared the desensitizing efficacy of dentifrice containing 5% fluoro calcium phosphosilicate versus 5% calcium sodium phosphosilicate in participants with sensitive teeth. Materials and Methods: A total of 60 participants above 18 years of age with a history of DH who displayed a visual analog scale (VAS) score of ≥ 4 to both subjective and thermal sensitivity in at least two teeth at the qualifying as well as baseline visit were considered eligible. Participants were randomly allocated to one of the following dentifrices: 5% fluoro calcium phosphosilicate; 5% calcium sodium phosphosilicate; and a standard dentifrice containing fluoride. Sensitivity scores (VAS) were measured at baseline, immediately after scaling and root planning, at 15, 30, and at 60 days. Results: A statistically significant reduction in symptoms for all treatment groups from baseline to 15, 30, and 60 days for both measures of sensitivity was observed. A significant reduction in DH with time for all the variables during the 8 weeks of the active phase of the study independent of treatment groups was noted. However, the fluoro calcium phosphosilicate group showed a higher degree of effectiveness in reducing DH, followed by calcium sodium phosphosilicate then standard fluoride dentifrices. Conclusion: Under the conditions of a clinical trial, the fluoro calcium phosphosilicate group showed a comparable reduction in the symptoms of DH.